Linguistic Interpretation of Terminological Neologisms - Larina Kamila Petrovna (International Journal Of Literature And Languages, 2026)
This article investigates the linguistic nature of terminological neologisms, exploring the mechanisms behind their formation, semantic development, and functional incorporation into specialized discourse. Drawing on terminological theory, cognitive semantics, and corpus linguistics, the study puts forward a multi-dimensional analytical framework to explain the dynamic processes through which neologisms gain terminological standing within scientific and professional communities.